Literature and Medicine in the Nineteenth- Century Periodical Press Blackwood's Edinburgh Magazine, 1817-1858 - Coyer, Megan (Edinburgh University Press, 2017)
In the early nineteenth century, Edinburgh was the leading centre of medical education and research in Britain. It also laid claim to a thriving periodical culture, which served as a significant medium for the dissemination and exchange of medical and literary ideas throughout Britain, the colonies, and beyond. Literature and Medicine in the Nineteenth-Century Periodical Press explores the relationship between the medical culture of Romantic-era Scotland and the periodical press by examining several medically-trained contributors to Blackwood's Edinburgh Magazine, the most influential and innovative literary periodical of the era.